Antibodies to AMPA receptors in Rasmussen's encephalitis. (March 2016) - Nibber, Anjan; Clover, Linda; Pettingill, Philippa; Waters, Patrick; Elger, Christian E.; Bien, Christian G.; Vincent, Angela; Lang, Bethan
Abstract: Rasmussen's encephalitis is a rare progressive childhood disorder characterized by frequent severe seizures, hemiparesis, encephalitis and mental deterioration, and associated with severe unilateral neuroinflammation. Autoantibodies, particularly to the GluA3 subtype of the alpha-amino-3-hydroxy-5-methyl-isoxazole-4-propinonic acid receptor (AMPAR) were reported in the 1990s but not always confirmed. To explore further, sera from 52 patients with Rasmussen's encephalitis were tested by cell-based assays for antibodies to AMPAR GluA1/2/3, N-methyl-d -aspartate (NMDA NR1/2b), γ-aminobutyric acid type A and B (GABAA R α1/γ2/β2 and GABAB R b1/b2) receptors, for potassium channel complex proteins, and for binding to live cortical and hippocampal neuronal cultures. Two patients' sera (3.8%) bound to HEK cells co-transfected with the GluA2 and GluA3 subunits. One additional patient had a low level of VGKC-complex antibodies. These three, and seven additional, sera bound to hippocampal cultures. No other antibodies were detected. Thus, despite the rarity of GluA2/3 antibodies, 10 patients (19.2%) had evidence of antibodies to neuronal antigens. Whether these antibodies play a primary role in RE, or appear secondary to the neuro-inflammatory damage in this highly destructive disease, requires further study. Highlights: Fifty two patients with Rasmussen's Encephalitis were tested for antibodies to AMPA receptors using cell-based assays. Two patients (3.8%) had antibodies to AMPA receptors comprising of GluA2/3 co-expressed together. No sera showed reactivity to the singly transfected receptors (GluA1, 2 or 3) or to co-expressed GluA1/2. Ten patients (including both patients with antibodies that bound GluA2/3) bound to the surface of cultured neurones. The antibodies detected to GluA2/3 may represent a biomarker of the inflammatory nature of the disease.